Infant and maternal risk factors of severe acute malnutrition under 6 months of age - Sharma, Ashutosh Kumar; Das, Ghanshyam (Indian Journal of Child Health, 2020)
Aims: This study aims to analyze and focus on the factors associated with the risk of severe acute malnutrition (SAM) under 6 months infants. Materials and Methods: This hospital-based prospective study was conducted in the Department of Pediatrics of a Medical College in Central India from March 2019 to March 2020. Infant under 6 months of age admitted for SAM and related complications were observed during their stay in the hospital. After obtaining informed consent and detailed history including contributing factors, complete physical examination, anthropometry, comorbidities, and outcome were also recorded. SAM was classified according to the WHO criteria. Results: A total of 126 infants, 1–6 months of age, were enrolled in the study with a male-to-female ratio of 2.3:1. Birth weight (p=0.037), prematurity (p=0.0021), birth spacing (p=0.001), infant feeding characteristics as giving prelacteal feed (p=0.001), initiation of breastfeed after 1 h (p=0.003), exclusive breastfeeding (p=0.037), deprivation of colostrum (p=0.002), maternal characteristics age at first conception (p